The Development of Matching Game as Media to Teach Vocabulary for Elementary School Students - Nila Nofrita Hayati; Syahrul Syahrul (Universitas Pendidikan Indonesia Kampus Serang, 2021)
This research aimed at developing a learning media that can be used in the learning process at class V SDIT Syahiral Ilmi Bukittinggi. The media that developed was a matching game by using Adobe Flash CS6 to teaching vocabulary to young learners at the fifth grade Of SDIT Syahiral Ilmi Bukitinggi. This research was done because most students still encounter problems in learning English especially vocabulary mastery. Most of the students were difficult to memorize the new word, then the atmosphere of the classroom was not conducive and the students tend to be sleepy and bored in the classroom. Difficulties of students in understanding the material in learning English becomes a consideration for the researcher to develop the matching game as media to teach vocabulary to young learners. The research design was Research and Development (R D), by using ADDIE models that consist of: (1) analysis, (2) design, (3) development, (4) implementation, and (5) Evaluation. The researchers have limited this research because in the Covid-19 pandemic time, therefore this research was done until only the Implementation stage. The data collection was obtained by validation results from learning media experts. The result of two media experts showed the percentage score was 94% in the “valid” category, while from the teacher as material experts showed 84% which was “valid” criteria as well as from language experts obtained percentage to 86% include “valid” category. Based on the result of analyzing data the media of matching game was feasible to be used in teaching and learning English.